The slave trade in Algeria during the late Ottoman era and the beginning of French colonization through archival documents - Akram, Boudjemaa; Djemaa, Benzeroual; Quafia, Nafti; Assia, Bezzalla (The International tax journal, 2025)
Research background: This study aims to provide a historical overview of the social and economic conditions of Algeria during the late Ottoman era and the beginning of French colonization, with a focus on the enslaved class in Algerian society. We have divided this study into two sections: the conditions of the enslaved in the northern cities during the Ottoman era, and the conditions of the enslaved in southern Algeria, highlighting the main trade routes, stations, and the important products brought from sub-Saharan Africa. We then examined France's stance on the slave trade in Algeria after the colonization, including the position of the French government and the attitudes of slave traders, relying on several French archival documents. Additionally, we discussed the drawbacks and benefits of the French documentation and its historical and economic value in the history of Algeria during the 19th century. Purpose of the article: The purpose of the article is to address key issues, which are: How was the slave trade practiced in Algeria during the late Ottoman era?, What were the major sources of slavery in Algeria and its commercial centers?, What was the stance of French colonization towards this human trafficking?